A study of corrosion of impellers drinking water pumps in Al-Sin spring - مسلم همام; علي هترة; عزت حسن (Latakia University Journal -Engineering Sciences Series, 2023)
This research aims to describe the corrosion occurring in the bronze impellers of the water pumps of Al-Sin Spring of the classification (Cu SN10-C-GC) according to the DIN system, where the form of corrosion occurred and the factors causing it were studied, Including the chemical factor resulting from the water sterilization material, and the mechanical factor resulting from the friction of filter sand atoms with the blades, and the most harmful areas in the body of the impellers were identified, and when calculating the corrosion rates, whether the rate of decrease in thickness, decrease in weight, or the coefficient of pitting corrosion. It was observed that corrosion records dangerous values, which significantly affected the pumps’ yields in terms of the amount of water produced. In the corrosion study, actual samples of out-of-service pump impellers were relied upon, and the results were compared with samples of new impellers The recommendations of the manufacturer of the pumps, OMEGA/KSB, were also used to find out the life span of the impeller, and compare them with the actual age, as a significant deviation was noticed in the actual result from the assumed one, which entails large financial and technical burdens on the work of the pumping group.